Perbandingan Perhitungan, Penyetoran, dan Pelaporan Pajak Penghasilan (PPh) Badan menurut Undang-Undang no 36 tahun 2008 dan Peraturan Pemerintah No 46 Tahun 2013 pada PT XXX - M. Wahyudi; Ely Kartikaningdyah (JURNAL AKUNTANSI, EKONOMI dan MANAJEMEN BISNIS, 2014)
This research was conducted at PT XXX for the enactment of changes in tax laws in 2013 on a taxpayer that is on the comparison calculation, deposit, and the reporting of income tax (VAT) Agency in accordance with law No. 36 of 2008 and Government Regulation No. 46 year 2013 of PT XXX. The purpose of this study was to calculate and compare the calculation, deposit and report tax (income tax) Agency in accordance with the new regulations. In this study the author uses descriptive method that describes the calculations and procedures for calculation of income tax (VAT) body in accordance with the new rules and regulations for long. The results of this study, authors can create a scientific paper that contains procedures for calculation, deposit, and tax reporting in accordance with applicable regulations